Implementasi Algoritme SHA-256 Menggunakan Protokol MQTT pada Budidaya Ikan Hias - Yogi Anugrah; Mochammad Hannats Hanafi Ichsan; Ari Kusyanti (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Message Queue Telemetry Transport (MQTT) is one of the communication protocols used in the Internet of Things (IoT) device. The MQTT protocol is often used because this protocol requires low resources and the small size of the data sent. Although Secure Socket Layer (SSL) can be applied to secure the MQTT protocol, it requires large processing resources. Therefore another solution is needed that does not burden the system such as implementing the HMAC algorithm. The commonly used HMAC algorithm comes from hash algorithms such as SHA-1. But the SHA-1 algorithm has been declared unsafe and vulnerable to brute force and collision attacks. Therefore the SHA-256 algorithm is used as an update of SHA-1 which is resistant to brute force and collision attacks. Based on the system security testing that has been applied using HMAC-SHA256, the system can find out if there is a change, substitution, or data insertion. While the performance of HMAC-SHA256 was obtained from a performance test consisting of testing the making of HMAC-SHA256 and testing memory usage. The average time needed to make HMAC-SHA256 is 604,958 ms in the publisher and 606,703 ms in the subscriber. Increased memory usage without and when using HMAC-SHA256 for 0,0078 MB in the publisher and 0,0082 MB on the subscriber.